Novel kinetic and developmental transcriptomic pan-stress responses by embryonic stem cells - Aditi Singh; Ximena Lu Ruden; Wen Tang; Awoniyi Olumide Awonuga; Douglas Mark Ruden; Steven James Korzeniewski; Elizabeth Ella Puscheck; Hao Feng; Daniel Allen Rappolee (Scientific Reports)
Abstract Embryo development is highly susceptible to environmental stressors, contributing significantly to early miscarriages in 70% of human embryos (Cross et al. in Science 266:1508–1518, 1994, Macklon et al. in Hum Reprod Update 8:333–343, 2002). Yet the underlying mechanisms remain poorly understood. Here, we employ mouse embryonic stem cells (ESC) as a model to identify shared “pan-stress” markers for responses to diverse environmental insults implicated in miscarriage (Puscheck et al. in Birth Defects Res 114:1014–1036, 2022, Puscheck et al., in: Leese HJ, Brison DR (eds) Cell Signaling During Mammalian Early Embryo Development, Springer, New York, 2015 ). ESC were exposed to control stimuli and diverse stressors at previously characterized risk levels for growth, mimicking miscarriage risk exposures, then subjected to transcriptomic analysis via RNA sequencing. Surprisingly, we identify a large, substantial set of significantly-changing genes—termed pan-stress genes that also exhibited concordant changes in directionality compared to initial stemness. These genes show significant differential expression across stress conditions, distinguishing weak and strong stressors. Notably, ninety-four genes display significant expression changes under four weaker stressors and normal differentiation conditions, while a twenty-one/ninety-four gene subset exhibits shared significance with the inclusion of two stronger stimuli. Importantly, all identified pan-stress genes, the set of ninety-four and subset of twenty-one, exhibit 100% concordant, highly nonrandom directional changes from the initial stemness. Transcription and secreted factors that might mediate nonrandom concordant stress response were identified. These findings characterize a robust pan-stress response in ESC, suggesting potential biomarkers for miscarriage prediction and testing of underlying mechanisms.